The Efforts to Improve Student Learning Outcomes Through Learning Models Cooperative Using Student Study Worksheets: Upaya Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Kooperatif Menggunakan Lembaran Tugas Belajar Siswa - Hayatun Nufus (Journal of Vocational Education and Information Technology (JVEIT), 2021)
Student learning activity is still low and student learning outcomes are still in the average range or have not reached the maximum value as expected. This makes the teacher to find the right solution so that the student's score is in accordance with what is expected. Especially in chemical elements which is taught in class XII IPA TP 2017/2018, this material is classified as boring, needs analysis and a broad coverage that requires students to be able to understand and memorize and analyze carefully. Learning with the lecture method has not made students able to understand the concept well. Conditions that challenge students to be involved and more active in the learning process One way that can be done is to increase student involvement in learning through the application of the Cooperative Learning model using student learning assignments. The implementation of this research consisted of two cycles with each cycle consisting of four meetings. The first meeting students learned using the lecture method, and student activities were observed by an observer. The next meeting was given a student learning assignment sheet. As a data collection tool was an observation sheet which filled by observers, with the steps for planning the action, implementing the action, evaluating and reflecting on each cycle. From the research, it was found that there was an increase in activity and student learning outcomes using cooperative learning models using student learning assignments.Keyword : Learning activities, learning outcomes, cooperative learning models